DeMorgan's law

Dave

Joined Nov 17, 2003
6,970
Two points:

1. Aquaint yourself with DeMorgan's Theorums.

2. Remember that you can apply the double-NOT function such that it will not change the expression, i.e. A => NOT gives A' => NOT gives A (where ' = NOT). This is very useful when applying DeMorgan's Theorums.

Have a go, post up your attempts and we can help you from there.

Dave
 

thingmaker3

Joined May 16, 2005
5,084
Did you read the information in the link? If you can cite the specific parts you are having trouble with, we can walk you through them.
 

emad

Joined Mar 26, 2007
6
DEAR
you can use simple one law

( A . B )' = A' + B'


A( B. C' +(D.E)' )+ (B.F)' =

A( B. C' + D' + E' ) + B' + F' =

A . B . C' + A .D' + A .E' + B' + F'
 
Top